Karakater Nabi Ismail Dalam Al Quran: (Kajian Tafsir Tematik) - Misbahul Munir; Wasiul Maghfiroh (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2023)
The main issue raised in this paper is the interpretation of the verses that explain the character of the Prophet Ismail. Looking at the reality of life, there are many phenomena of juvenile delinquency that are caused by a lack of morals and parental upbringing, so that social deviations often occur in the community or changes in children's attitudes. This research aims to provide education to the public, especially to teenagers and parents so that they always act with good morals as mentioned in the story of Prophet Ismail and the character possessed by Prophet Ismail. This paper uses the type of research library research, which collects data and information from various kinds of literature. The type used in this study is a type of qualitative research so as to produce descriptive data. While the method used in data collection is the thematic method, which is a method that covers a broad interpretation by directing it to a particular theme. The results of this study are that the character of the story of Prophet Ismail is found in surah As-S{affa>t verses 101-107 and surah Al Baqarah verses 125 and 127. In these verses, data is obtained about the character of Prophet Ismail, namely the nature of patience, obedience to God and parents, courteous in words and deeds and sincere in accepting and carrying out God's commands. So that these characters can be applied to society, especially Muslim youth. by implementing several ways, including by inviting him to have a good dialogue that includes religious learning in it, advising him when he makes a mistake, making promises accompanied by persuasion and seduction when the child is about to do something bad, and giving a warning when the child commits a prohibited act.